Case Report: CD19 and CD22 CAR-T therapy induced durable complete remission in a patient with refractory plasmablastic lymphoma - Liu, Dan; Wei, Haichen; Hu, Yanran; Wang, Hui; Li, Ping; Lu, Ke; Zhang, Wenjun; Xing, Lijie; Li, Zengjun (Frontiers in Immunology, 2025)
IntroductionPlasmablastic lymphoma (PBL) is a rare and highly aggressive form of non-Hodgkin lymphoma that is associated with a poor prognosis. Traditional chemotherapy has demonstrated limited efficacy for PBL. There is currently no standard treatment for patients with refractory or relapsing PBL. While CAR-T therapy has shown promising outcomes in leukemia, lymphoma and myeloma, evidence of its application in PBL remains scarce.Case presentationWe describe a 56-year-old patient diagnosed with PBL. The patient achieved short-term remission with bortezomib in combination with etoposide, dexamethasone, cyclophosphamide, and doxorubicin as first-line therapy. After disease progression, the patient received daratumumab combined with GemOx as second-line treatment but showed no response. Tumor biopsy after disease progression revealed strong positive CD22 and partial positive CD19 expression. The patient received CD19 and CD22 CAR-T therapies as the third-line treatment and achieved durable complete remission for more than one year with good tolerance.ConclusionA patient with refractory PBL achieved durable complete remission after CD19 and CD22 CAR-T therapies, suggesting this treatment may be effective for patients with refractory or relapsing PBL.